2021
DOI: 10.1002/mp.15356
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous dose and dose rate optimization (SDDRO) of the FLASH effect for pencil‐beam‐scanning proton therapy

Abstract: Purpose Compared to CONV‐RT (with conventional dose rate), FLASH‐RT (with ultra‐high dose rate) can provide biological dose sparing for organs‐at‐risk (OARs) via the so‐called FLASH effect, in addition to physical dose sparing. However, the FLASH effect only occurs, when both dose and dose rate meet certain minimum thresholds. This work will develop a simultaneous dose and dose rate optimization (SDDRO) method accounting for both FLASH dose and dose rate constraints during treatment planning for pencil‐beam‐sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…As such, it would not be straightforward to directly optimize the FLASH dose reduction using our framework. However, our presented FLASH effectiveness model is independent of the used optimizer, and thus it would be possible to include this model into the cost function of any other optimizer, resulting in a similar framework as the simultaneous dose and dose rate optimizer recently presented by Gao et al 26 In summary, our model is the first quantitative representation of previous findings, that is, that transmission plans and fewer treatment fields are likely to induce higher FLASH effects than conventional planning scenarios. 12 The sensitivity analysis additionally revealed that, in order to achieve a clinical benefit of the transmission plan compared to the clinical reference plan, hypofractionated treatments with increased fraction doses will be required.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…As such, it would not be straightforward to directly optimize the FLASH dose reduction using our framework. However, our presented FLASH effectiveness model is independent of the used optimizer, and thus it would be possible to include this model into the cost function of any other optimizer, resulting in a similar framework as the simultaneous dose and dose rate optimizer recently presented by Gao et al 26 In summary, our model is the first quantitative representation of previous findings, that is, that transmission plans and fewer treatment fields are likely to induce higher FLASH effects than conventional planning scenarios. 12 The sensitivity analysis additionally revealed that, in order to achieve a clinical benefit of the transmission plan compared to the clinical reference plan, hypofractionated treatments with increased fraction doses will be required.…”
Section: Discussionmentioning
confidence: 82%
“…As such, it would not be straightforward to directly optimize the FLASH dose reduction using our framework. However, our presented FLASH effectiveness model is independent of the used optimizer, and thus it would be possible to include this model into the cost function of any other optimizer, resulting in a similar framework as the simultaneous dose and dose rate optimizer recently presented by Gao et al 26 …”
Section: Discussionmentioning
confidence: 99%
“…They include simple parameter thresholds, such as dose, dose rate and dose rate volume histogram thresholds and aim typically to quantify voxels or a dose fraction per voxel that fulfil these criteria, assuming a binary FLASH effect [115,[118][119][120][121]. Furthermore, more complex metrics, such as dose-averaged dose rate and '95% of the dose in a voxel delivered within a certain time', have been proposed for UHDR treatments with a more complex delivery time structure, such as scanned beams delivered via multiple portals [75,115,119,[122][123][124]. While latter metrics have been developed in the context of UHDR PT, they could be equally applied to UHDR electron beam RT.…”
Section: Accounting For the Flash Effect In Uhdr Electron Treatment P...mentioning
confidence: 99%
“…D CONV , is the dose delivered in UHDR mode, resp. in CONV mode, for an isoeffect for the tumor) [75,120,123,126]. This has been used by some treatment planning studies either using generic DMF factors [97,120,123,127] or utilising a modelling based on the radiolytic oxygen depletion hypothesis [75].…”
Section: Accounting For the Flash Effect In Uhdr Electron Treatment P...mentioning
confidence: 99%
See 1 more Smart Citation